Analysis of publicly available geocoding tools and their application within the ALM institutions (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. The paper aims to present to the broader ALM community the available geocoding tools that can be useful for presenting diverse collections related to a particular area. The paper will discuss a few publicly available tools and outline their advantages and disadvantages, application possibilities, and accessibility.Approach/methodology/design. The paper theoretically defines the basic terms that the authors of virtual exhibitions and interactive maps encounter (GIS, mapping, geocoding, and geolocation). The paper presents a comparison of seventeen publicly available geocoding tools using an analysis that considers the advantages, disadvantages, institutions for which they are intended, and price.Findings. There were 17 geocoding tools analyzed. Of the 17 observed tools, 10 of them have a wide spectrum of application, which, in the author's opinion, also includes the ALM community. The results provide information on the advantages, disadvantages, price and purpose (that is, users) of the observed tools, and the possibilities of their application. Performances of the mentioned tools, such as simplicity of the user interface, open code, transparency, the durability of access and the price ranges were taken in consideration.Research limitations/implications. The large number of publicly available geocoding tools as well as their continuous development make analysis difficult. Despite the detailed familiarization, not all analyzed geocoding tools were used by the authors, only some of them, which leaves the possibility that some advantages or disadvantages were overlooked.Practical implications. The paper presents publicly available geocoding tools that can be useful for the promotion of digital collections in an interactive and popular way.Originality/value. The value of this paper is reflected in the fact that publicly available geocoding tools are included and analyzed in one place. The analysis can be used as a template for comparison before deciding on the selection of the appropriate geocoding tool for creating an interactive map based on the digital collection of a certain ALM institution.
Keywords: ALM community; digital collections; geocoding tools; interactive maps